Korelasi Nilai Kognitif, Psikomotor dan Afektif pada Mata Kuliah Fisika Dasar II Mahasiswa Pendidikan Fisika Angkatan 2017 - Rohana; Yusrizal; Tarmizi (Journal of Technology and Literacy in Education, 2022)
This study aims to find out the correlation between cognitive values and psychomotor and affective values on Basic Physics II. The type of research is correlational with a quantitative approach. The research subjects were 23 second semester students of class B of 2017. The data collection technique uses a test by giving questions consisting of 1 essay question, performance assessment rubric consisting of 11 assessment criteria, and attitude scale (Likert scale) consisting of 25 statements. Data were analyzed using coefficient of multiple correlation, coefficient of multiple determination and statistical hypothesis testing using F-test. The results of data analysis showed 15%, of coefficient of multiple determination. Coefficient of multiple correlation between cognitive values and psychomotor and affective values was R_(y〖 x_1 x〗_(2 ) )= 0,387 and categorized as low or weak correlation and the result of hypothesis testing showed Fcal < Ftable or 1,5 < 3,59 thus H_o is accepted meaning that there is no significant correlation between cognitive values and psychomotor and affective values on Basic Physics II.